Speech prosody impairment predicts cognitive decline in Parkinson's disease - Rektorova, Irena; Mekyska, Jiri; Janousova, Eva; Kostalova, Milena; Eliasova, Ilona; Mrackova, Martina; Berankova, Dagmar; Necasova, Tereza; Smekal, Zdenek; Marecek, Radek (Parkinsonism & related disorders, 2016)
BACKGROUND: Impairment of speech prosody is characteristic for Parkinson's disease (PD) and does not respond well to dopaminergic treatment. OBJECTIVES: We assessed whether baseline acoustic parameters, alone or in combination with other predominantly non-dopaminergic symptoms may predict global cognitive decline as measured by the Addenbrooke's cognitive examination (ACE-R) and/or worsening of cognitive status as assessed by a detailed neuropsychological examination. METHODS: Forty-four consecutive non-depressed PD patients underwent clinical and cognitive testing, and acoustic voice analysis at baseline and at the two-year follow-up. Influence of speech and other clinical parameters on worsening of the ACE-R and of the cognitive status was analyzed using linear and logistic regression. RESULTS: The cognitive status (classified as normal cognition, mild cognitive impairment and dementia) deteriorated in 25% of patients during the follow-up. The multivariate linear regression model consisted of the variation in range of the fundamental voice frequency (F0VR) and the REM Sleep Behavioral Disorder Screening Questionnaire (RBDSQ). These parameters explained 37.2% of the variability of the change in ACE-R. The most significant predictors in the univariate logistic regression were the speech index of rhythmicity (SPIR; p = 0.012), disease duration (p = 0.019), and the RBDSQ (p = 0.032). The multivariate regression analysis revealed that SPIR alone led to 73.2% accuracy in predicting a change in cognitive status. Combining SPIR with RBDSQ improved the prediction accuracy of SPIR alone by 7.3%. CONCLUSIONS: Impairment of speech prosody together with symptoms of RBD predicted rapid cognitive decline and worsening of PD cognitive status during a two-year period.
Keywords: Speech Disorders; neparametrická statistika; Humans; neuropsychologické testy; Longitudinal Studies; lidé středního věku; Acoustic analysis; řeč; Female; Aged; Speech; senioři; lidé; Parkinson’s disease; Cognition Disorders; Neuropsychological Tests; ženské pohlaví; longitudinální studie; Cognitive; Male; Middle Aged; poruchy řeči; Aged, 80 and over; Dementia; Statistics, Nonparametric; Statistics as Topic; Speech prosody; senioři nad 80 let; kognitivní poruchy; mužské pohlaví; statistika jako téma; Parkinson Disease; Parkinsonova nemoc